THE ROLE OF LOCAL GOVERNMENT IN ADDRESSING THE IMPACT OF INFLATION AND INTEREST RATES ON GOLD PRICES AT THE SUNGUMINASA BRANCH OF THE PAWNSHOP IN GOWA REGENCY - Nurjayanti; Eka Fitra Ramadhani; Yudhi Andrew Pratama Lumoindon (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the role of local government in responding to the influence of inflation and interest rates on gold prices at the Pegadaian Sungguminasa Branch, Gowa Regency. The data used in this research were obtained from the period 2021 to 2023. The study employs a descriptive quantitative method with a case study approach at Pegadaian Sungguminasa Branch. Data were collected through documentation and interviews with relevant parties, including local government officials and Pegadaian management. The results show that fluctuations in inflation and interest rates have a significant effect on changes in gold prices. The local government plays an important role in maintaining economic stability through inflation control policies, improving financial literacy among the community, and collaborating with financial institutions such as Pegadaian to provide safe and productive investment access for the public. This research is expected to serve as a reference for local governments in formulating adaptive economic policies in response to macroeconomic dynamics, particularly those related to gold prices.